DEMOCRACY, ETHICS OF STATE AND GENERAL PRINCIPLES OF GOOD GOVERNANCE: AN EXAMINATION OF THE EXERCISE OF POWER IN INDONESIA - Fajari, Ghiska; Setiadi, Wicipto (Fakultas Hukum Universitas Swadaya Gunung Jati, 2024)
Democracy provides a view that power comes from the people. State ethics and the application of general principles of good governance (AAUPB) are two important pillars that support the integrity and credibility of a country. This research focuses on how democracy, state ethics and AAUPB are aligned and how democracy, state ethics and AAUPB are implemented in Indonesia. By prioritizing the values of democracy, civic ethics, and AAUPB, we can create an environment that supports and strengthens democracy and serves the common good. In the exercise of power in Indonesia, it is important to ensure that democracy is exercised with civic ethics and follows AAUPB so that the government runs well and in accordance with the interests of the people.